PEMBUATAN APLIKASI GAME PENGOLAHAN KATA DENGAN MEDIA GAMBAR BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract   In the development of increasingly advanced technology, mobile phones have become a necessity for all classes, both old and young, even children. Functions of the phone can be different for a person depending on their respective needs. Mobile or what is now often referred to as smartphones changed the function of communication tools into media entertainment, especially for gaming. Games are not only used for entertainment alone but can be used as a medium of learning, with the making of the application that the author made to attract children in knowing the names of the fruit with the media image that is in it. Here the authors conducted research on Earth Village Nursery Raji, Village Raji District of Demak. This study aims to help improve memory of children to the images, especially fruits with word processing tools. To facilitate the child in answering the question, in this application 3-assisted display random characters and how the number of characters that should fill in on the image displayed.   Keywords: Game, Education.